Effects of tapeworm infection on absorption and excretion of zinc and cadmium by experimental rats - Sloup, Vladislav; Jankovská, Ivana; Száková, Jiřina; Magdálek, Jan; Sloup, Simon; Langrová, Iva (Environmental science and pollution research international, 2018)
The main objective of this study was to determine how rat tapeworms affect the excretion of zinc and cadmium through rat feces. Male rats (Rattus norvegicus var. alba) were divided into four groups, and the experiment was conducted over a 6-week period. The control groups (00; 0T) were provided with a standard ST-1 rodent mixture and received 10.5 mg of Zn/week. Groups P0 and PT were fed a mixture supplemented with the hyperaccumulating plant Arabidopsis halleri at a dosage of 123 mg Zn/week and 2.46 mg Cd/week. Groups 0T and PT were infected with the rat tapeworm (Hymenolepis diminuta). Fecal samples were collected 24 h post exposure. Zinc and cadmium concentrations in rat feces were analyzed using inductively coupled plasma optical emission spectrometry. Tapeworm presence decreased the amount of metals excreted through the feces of the host throughout the entire experiment, with the exception of 1 week (control group). No statistically significant differences between zinc excretion rates in the control groups (00 and 0T) were detected at any time throughout the experiment. A statistically significant difference between zinc excretion rates (p < 0.05) in the exposed groups (P0 and PT) was detected in 2 of the 6 monitored weeks. Group PT excreted significantly less cadmium (p < 0.01) than group P0 did in three of the 6 weeks. Overall, our results indicate that tapeworms are able to influence the excretion of metals by their host. Tapeworms accumulate metals from intestinal contents. It is not clear whether tapeworms carry out this process before the host tissues absorb the metals from the intestines or the tapeworms accumulate metals excreted from the body of the host back to the intestines. Most likely, it is a combination of both phenomena.
Keywords: krmivo pro zvířata; cestodózy; modely nemocí na zvířatech; Environmental Pollutants; Rat; Hyperaccumulators; kadmium; zvířata; feces; Excretion; Disease Models, Animal; Animal Feed; Cadmium; látky znečišťující životní prostředí; mužské pohlaví; Gastrointestinal Contents; Feces; Hymenolepis diminuta; zinek; Tapeworm; Rats, Wistar; gastrointestinální obsah; potkani Wistar; Animals; Zinc; Male; Cestode Infections